Creating learning schools through learning-centered leadership: Understanding the moderating role of teacher performance - Alanoglu, Muslim (Sage Publications Ltd, 2025)
How learning-centered leadership influences learning schools, and the effect of teacher performance on building learning schools is an area that remains unclear. The study aims to investigate the effect of learning-centered leadership on learning schools from teachers' perspectives. In the cross-sectional study, survey data were collected from 284 teachers in 50K-12 schools in Elazig, Turkiye. Structural equation modeling and bootstrapping method were used to analyze the data. Data analysis revealed that learning-centered leadership elicited direct and indirect effects on building learning schools and that teacher performance was a mediator in this relationship. Results contribute to the body of research that confirms the role of learning-centered leadership in the emergence of learning schools that also enables school improvement and effectiveness and highlights the importance of reflecting on this relationship.
Keywords: Learning-centered leadership; principal; teacher performance; learning school